The Use of English Songs to Teach Pronunciation to the Tenth Graders of SMA Negeri 1 Gedeg Mojokerto - Nasirudin Nasirudin (LP3M STITNU AL HIKMAH MOJOKERTO, 2019)
Pronunciation is one of the important parts in learning English. Pronunciation is needed to accomplish the purpose of oral communication between the speaker and the listener (Hismanoglu, 2006). Therefore, by mastering pronunciation skills the English learner could minimize misunderstanding when they are communicating with other people. However Indonesian students especially in Senior High School still get difficulties in pronouncing the words correctly. It is difficult for Indonesian students to pronounce English word correctly. It is due to the difference between their first language and the target language. The fact above is caused by the way how the teacher teaches the students. Most teachers do not pay attention to the importance of pronunciation. According to harmer (2001:183), teachers feel that they already do a lot of things in teaching pronunciation. Yet, teachers in Indonesia do not know exactly how to teach pronunciation well. They prefer to ask their students to pronounce several words that could make the students bored. As a teacher, they do not only create a good atmosphere during teaching learning activity, but also create a joyful teaching technique. This research is descriptive qualitative research. The instrument used to gain the data of this research is observation checklist and interview. The description of the observation checklist includes: (1) The implementation of English songs to teach pronunciation in the tenth grader of SMA Negeri 1 1 Gedeg Mojokerto and (2) The students’ pronunciation result during the implementation of English songs in teaching pronunciation. The subject of this research is the students of class X-MIPA7 and the English teacher of SMA Negeri 1 Gedeg Mojokerto. The result of this study showed that the teacher’s implementation of English songs to teach pronunciation ran well. It is showed by the observation result that showed the enthusiasm of the students’ while the teacher gives them songs to learn English.It also showed that English songs as media could assist the students pronunciation. It could be seen from the number of students who were placed in the good to average category. They pronounced the vowel and consonant almost correct all the time. In short, English Songs could be used to teach pronunciation, especially to the students of tenth grade. It could be even used to create a good atmosphere inside the class while teaching and learning activity is running. For the next researcher who will conduct the similar research by using song as a media to teach pronunciation should chose the appropriate song based on the students ability.